Anterior shift of the ventral dura mater: A novel concept of the posterior surgery for ossification of the posterior longitudinal ligament in thoracic spine - Takahashi, Kohei; Hashimoto, Ko; Onoki, Takahiro; Kanno, Haruo; Ozawa, Hiroshi; Aizawa, Toshimi (Frontiers in Surgery, 2023)
Background: Thoracic myelopathy caused by ossification of the posterior longitudinal ligament (OPLL) remains one of the most difficult disorders to treat. The Ohtsuka procedure, extirpation, or anterior floating of the OPLL through a posterior approach, has shown great surgical outcomes after several modifications. However, these procedures are technically demanding and pose a significant risk of neurological deterioration. We have developed a novel modified Ohtsuka procedure in which removal or minimization of the OPLL mass is unnecessary; instead, the ventral dura mater is shifted anteriorly with the posterior part of the vertebral bodies and targeted OPLL. Methods: Eighteen patients (follow-up ≥1 year) treated with our modified Ohtsuka procedure were assessed clinically, including the Japanese Orthopaedic Association (JOA) score for thoracic myelopathy and radiographically. Results: The average follow-up period was 3.2 years (range, 1.3 – 6.1 years). The preoperative JOA score was 2.7±1.7, which improved to 8.2±1.8 at 1 year postoperatively; therefore, the recovery rate was 65.8±19.8%. The CT scan at 1 year after surgery revealed the anterior shift of the OPLL averaged 3.1±1.7 mm and the ossification-kyphosis angle of the anterior decompression site decreased at an average of 7.2±6.8 degrees. Three patients demonstrated temporary neurological deterioration, all of whom completely recovered within 4 weeks postoperatively. Discussion: The concept of our modified Ohtsuka procedure is 1) not OPLL extirpation or minimization but only the creation of space between the OPLL and spinal cord by an anterior shift of the ventral dura mater, which is achieved by complete resection of the PLL at the cranial and caudal sites of the OPLL; and 2) no nerve roots are sacrificed to prevent ischemic spinal cord injury. This procedure is not technically demanding and safe and provides secure decompression for thoracic OPLL. The anterior shift of the OPLL was smaller than expected, but it resulted in a relatively good surgical outcome with a recovery rate ≥65%. Conclusion: Our modified Ohtsuka procedure is quite secure and is not technically demanding, with a recovery rate of 65.8%.